CCR5 as a Treatment Target in Pulmonary Arterial Hypertension - Amsellem, Valérie; Lipskaia, Larissa; Abid, Shariq; Poupel, Lucie; Houssaini, Amal; Quarck, Rozenn; Marcos, Elisabeth; Mouraret, Nathalie; Parpaleix, Aurélien; Bobe, Régis; Gary-Bobo, Guillaume; Saker, Mirna; et al. (Circulation (New York, N.Y.), 2014)
BACKGROUND—Pulmonary arterial hypertension (PH), whether idiopathic or related to underlying diseases such as HIV infection, results from complex vessel remodeling involving both pulmonary artery smooth muscle cell (PA-SMC) proliferation and inflammation. CCR5, a coreceptor for cellular HIV-1 entry expressed on macrophages and vascular cells, may be involved in the pathogenesis of PH. Maraviroc is a new CCR5 antagonist designed to block HIV entry. METHODS AND RESULTS—Marked CCR5 expression was found in lungs from patients with idiopathic PH, in mice with hypoxia-induced PH, and in Simian immunodeficiency virus–infected macaques, in which it was localized chiefly in the PA-SMCs. To assess the role for CCR5 in experimental PH, we used both gene disruption and pharmacological CCR5 inactivation in mice. Because maraviroc does not bind to murine CCR5, we used human-CCR5ki mice for pharmacological and immunohistochemical studies. Compared with wild-type mice, CCR5 mice or human-CCR5ki mice treated with maraviroc exhibited decreased PA-SMC proliferation and recruitment of perivascular and alveolar macrophages during hypoxia exposure. CCR5 mice reconstituted with wild-type bone marrow cells and wild-type mice reconstituted with CCR5 bone marrow cells were protected against PH, suggesting CCR5-mediated effects on PA-SMCs and macrophage involvement. The CCR5 ligands CCL5 and the HIV-1 gp120 protein increased intracellular calcium and induced growth of human and human-CCR5ki mouse PA-SMCs; maraviroc inhibited both effects. Maraviroc also reduced the growth-promoting effects of conditioned media from CCL5-activated macrophages derived from human-CCR5ki mice on PA-SMCs from wild-type mice. CONCLUSION—The CCL5-CCR5 pathway represents a new therapeutic target in PH associated with HIV or with other conditions.